Інституційні аспекти розподілу державних доходів у рамках бюджетного простору регіонів - Тарангул, Л.Л.; Хомяк, М.С. (Економіка промисловості, 2017)
Досліджено наявний теоретичний доробок щодо інституційних аспектів процесу розподілу доходів у рамках бюджетного простору як результату фіскальної децентралізації; проаналізовано відповідний досвід окремих країн світу. Рассмотрены существующие теоретические исследования, связанные с институциональными аспектами процесса распределения доходов в рамках бюджетного пространства как результата фискальной децентрализации; проанализирован соответствующий опыт отдельных стран мира. The article examines existent theoretical background concerning main institutional aspects of distribution of state revenue in the framework of budget space as a result of fiscal decentralization process. Also we have briefly analyzed the experience of some countries relating to the creation and functioning of institutes, which facilitate the process of distribution of budget revenue across regions in the form of intergovernmental transfers.The research provided allowed us to conclude that in any system of public finance the sources of external financing of regional development by means of intergovernmental transfers play an important role. The main challenge is to structure them by such a way which does not limit the financial autonomy of local authorities, and at the same time which allows to eliminate fiscal imbalances that appear in the budget space due to specifics of regional development and present system of distribution of both budget and fiscal powers.The analysis of international experiences proved that the main tasks of such institutes as independent agencies facilitating the process of proving intergovernmental transfers and aimed to ensure the transparency, equity and accountability of intergovernmental financial system are difficult to implement in practice. The evidence shows that such agencies complicate and enhance the inequality of budget system that in turn leads to the increase of transaction costs and undermine the sustainability of political consensus.